2023
DOI: 10.1007/978-3-031-14360-1_4
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Structural Inequalities from a Socio-Legal Perspective

Abstract: This chapter critically analyses different socio-legal phenomena through a feminist prism on gender. With an aim to promote gender equality, it addresses the problems of structural gender inequalities in both private and public social spheres. Outlining the political, economic and ideological connection between laws and specific social contexts, it uncovers (hidden) effects of social reproduction and construction of gender and sexuality. Deconstructing the gender binary system and provoking a heterosexual matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, customary norms sometimes overrule legislative laws, exacerbating gender inequities (Gostin et al, 2019). (Bermúdez Figueroa et al, 2023;Yetiş & Bakırlıoğlu, 2024) also revealed the prevalence of structural barriers, including cultural biases, limited educational and training options, and strongly embedded gender stereotypes.…”
Section: Theories Underpinning the Studymentioning
confidence: 99%
“…Furthermore, customary norms sometimes overrule legislative laws, exacerbating gender inequities (Gostin et al, 2019). (Bermúdez Figueroa et al, 2023;Yetiş & Bakırlıoğlu, 2024) also revealed the prevalence of structural barriers, including cultural biases, limited educational and training options, and strongly embedded gender stereotypes.…”
Section: Theories Underpinning the Studymentioning
confidence: 99%